Cutaneous Blastomycosis and Systemic Findings. Issue 6 (November 2020) - Han, Jane J.; Lake, Eden
Abstract : ABSTRACT: Blastomycosis is a disease that has the ability to affect nearly any organ system, most commonly causing pulmonary disease. Diagnosis of blastomycosis therefore presents a unique problem for clinicians because of its diverse array of presentations. Cutaneous disease secondary to pulmonary disease may be the initial manifestation of blastomycosis. Cutaneous disease also has variable presentations from pustules to warty verrucous or ulcerated lesions. This article will focus on the cutaneous presentation of blastomycosis, including primary inoculation and secondary disseminated types, as well as other manifestations of blastomycosis in other organ systems. Diagnostic methods and general treatment guidelines will also be discussed.